Blood Subgroup of A Complicates Transfusion Workup in a Patient Who Receives Intravenous Immunoglobulin Therapy. (21st September 2018) - Nguyen, Luan; Kurtz, Justin; Lasky, Baia; Finck, Rachel
Abstract: Introduction: Intravenous immunoglobulin (IVIG) therapy is a potentially beneficial treatment for a wide range of medical disorders. One complication associated with IVIG is the passive transfer of donor antibodies, including those directed at RBC antigens, which may complicate immunohematologic workups. Methods/Results: We report a 49-year-old woman who presented with lower extremity weakness and ataxia and was found to have a large pelvic mass. The mass was classified as a primary fallopian tube serous carcinoma, and the patient's neurologic symptoms were felt to represent a paraneoplastic syndrome. Postoperatively, the patient was given a trial of 0.4 g/kg IVIG to treat these symptoms. After initiation of treatment, the patient's hemoglobin dropped from 9.0 to 7.6 g/dL, and an RBC transfusion was requested. Blood bank workup at that time demonstrated an ABO typing discrepancy; on forward type, the patient's RBCs agglutinated with anti-A and anti-B (blood group AB), but on reverse type, the patient's plasma agglutinated the reagent A cell (blood group B). Group AB, B, and A cells were all crossmatch incompatible. Group O RBCs were issued for transfusion, and an extensive workup for evidence of IVIG-associated passive transfer of isohemagglutinins with hemolysis was undertaken. A direct antiglobulin test (DAT) was microscopically positive for IgG but with a negative elution. No laboratory evidence of hemolysis could be found (normal values for bilirubin, LDH, haptoglobin) and a peripheral smear examination demonstrated RBCs with normal morphology. Finally, the patient's sample was assessed at a reference lab; the patient was determined to be a subgroup of A (blood group A2B, genotype A201/B101) with anti-A1 formation. Conclusion: This case demonstrates that although IVIG is known to cause hemolytic transfusion reactions and complicate immunohematologic workups, sometimes the most classic scenario may explain the laboratory findings.